A Review Of Positive Law and The Dsn-Mui Fatwa Number 144/DSN-MUI/XII/2021 On Electronic Trade Transactions in Sharia Marketplaces (Case Study of Ruang Halal and Muslim Lifeshop) - Siti Fatimatu Zahra; Abd Wahab Abd Muhaimin; Syarif Hidayatullah (Journal Research of Social Science, Economics, and Management, 2025)
The development of digitalization in Indonesia has driven significant market growth. As a country with the largest Muslim population in the world, Indonesia needs a marketplace that is in accordance with sharia principles. This study aims to analyze the suitability of electronic trade transaction practices in the Halal Space marketplace and the Muslim LifeShop marketplace with positive Indonesian legal rules and DSN-MUI Fatwa Number 144/DSN-MUI/XII/2021. This research uses a qualitative method in the form of a case study with a normative and empirical legal approach. Primary data is obtained through observation and interviews with the marketplace, while secondary data comes from laws and regulations, fatwas, and related literature. The results of the study show that the transaction mechanism in both marketplaces is in accordance with the provisions of electronic offering, electronic acceptance, and electronic confirmation in accordance with Government Regulation No. 80/2019. Both marketplaces have also fulfilled the principles and requirements of the salam contract from the perspective of Islamic law. However, there is a discrepancy in the seventh point of the DSN-MUI Fatwa No. 144/2021 because it still uses conventional banks in the virtual account payment option. This research contributes to the development of the digital halal ecosystem in Indonesia and becomes a reference for the development of a more comprehensive sharia marketplace.